2001
DOI: 10.1002/zoo.10028
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of gonadal and adrenal activity in the black and white rhinoceros in North America by noninvasive endocrine monitoring

Abstract: Patterns of fecal reproductive steroid metabolites and adrenal corticoids were characterized for 12-to 24-month periods in black (n = 10 male, 16 female) and white (n = 6 male, 13 female) rhinoceroses at 14 institutions. All black rhinoceros females exhibited at least some ovarian cyclicity on the basis of fecal progestogen analysis (range, 2-12 cycles/yr). However, cycles often were erratic, with many being shorter (<20 days; 18% of cycles) or longer (>32 days; 21%) than the average of 26.8 ± 0.5 days (n = 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
126
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(144 citation statements)
references
References 28 publications
(67 reference statements)
13
126
2
Order By: Relevance
“…These responses are similar to the moderate effects of ACTH reported for some ferrets, rhinoceroses, and chinchillas Young et al 2001;Ponzio et al 2004). As additional studies utilize exogenous glucocorticoid stimulants or suppressors, patterns of differential response as a function of species, population, sex, or individual will become more clear (Hubbs et al 2000;Teskey-Gerstl et al 2000;Brown et al 2001;Goymann et al 2001;Hik et al 2001;Young et al 2001). …”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…These responses are similar to the moderate effects of ACTH reported for some ferrets, rhinoceroses, and chinchillas Young et al 2001;Ponzio et al 2004). As additional studies utilize exogenous glucocorticoid stimulants or suppressors, patterns of differential response as a function of species, population, sex, or individual will become more clear (Hubbs et al 2000;Teskey-Gerstl et al 2000;Brown et al 2001;Goymann et al 2001;Hik et al 2001;Young et al 2001). …”
Section: Discussionsupporting
confidence: 71%
“…Although the results of study 2 revealed a correlation between basal concentrations of serum corticoids and fecal metabolites, it was necessary to demonstrate a temporal correlation between changes in adrenal activity and changes in glucocorticoid-metabolite levels in feces. In large mammals, an increase in fecal metabolite levels can be detected approximately 24-48 h after an ACTH challenge (Graham and Brown 1996;Monfort et al 1998;Goymann et al 1999;Wasser et al 2000;Brown et al 2001;Millspaugh et al 2002;Wielebnowski et al 2002;Mashburn and Atkinson 2004;Young et al 2004). In smaller mammals (<150 g), fecal glucocorticoid-metabolite levels typically increase within 24 h of stimulation of the adrenal glands or injection of labeled glucocorticoids (e.g., 6-12 h in house mice, deer mice, and red-backed voles [Harper and Austad 2000]; 8-24 h in common marmosets [Bahr et al 2000]; 20-44 h in black-footed ferrets [Young et al 2001]; 30 h in chinchillas [Ponzio et al 2004]).…”
Section: Study 3: Sensitivity Of Fecal Hormone Assay To Acth and Dex mentioning
confidence: 99%
“…The remaining values yielded the baseline 5-pregnan-3-ol-20-on concentration. Ovarian cycle length and periodicity was then determined according to the procedure described by Brown et al [45,47]. Phase length estimates as well as ovarian cycle length estimates are given as mean ± SD.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals were categorized as demonstrating periods of anestrus if they had a follicular phase lasting longer than twice the duration of an average normal follicular phase (≥ 10 weeks) [25,47]. Determination of pregnancy within treated cows was based on luteal phase lengths persisting longer than 3-5 months [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the species-specific differences in hormone metabolite excretion (Palme et al 1996;Busso et al 2005) and the presence of different steroid metabolites in the excreta of even closely related species (e.g. Berkeley et al 1997;Schwarzenberger et al 2000;Brown et al 2001), respective assays should be validated in terms of their applicability for the hormone matrix of interest to ensure a reliable quantification of respective hormone metabolites (Hodges et al 2010).…”
Section: Introductionmentioning
confidence: 99%